Coupling of strike-slip faulting and lacustrine basin evolution: sequence stratigraphy, structure, and sedimentation in the North Yellow Sea Basin (West Bay Basin offshore North Korea), eastern China. (October 2020) - Wang, Ren; Shi, Wanzhong; Xie, Xiangyang; Zhang, Xianping; Wang, Liaoliang; Manger, Walter; Busbey, Arthur B.
Abstract: The North Yellow Sea Basin in offshore areas of eastern China provides a unique opportunity to document the interaction between the paleo-Eurasian and circum-Pacific tectonic domains and the coupled relationship between Tanlu Fault strike-slip activity, intrabasinal tectonics and sedimentation. This study combines well data, three-dimensional (3-D), and two-dimensional (2-D) seismic data to make regional tectonics interpretations, and delineate the sequence stratigraphy, geological structure and sedimentary history of the basin's Eastern depression, particularly focusing on the influence of Tanlu Fault strike-slip activity on basin evolution. The Eastern depression data record the development of five second-order stratigraphic sequences, both the Mesozoic and the Cenozoic fault systems with basement F1, F2 and F3 faults, and the deposition of various deltaic, fan delta, lacustrine, and subaqueous fan facies associations. The F1 and F3 faults controlled the NW- and NE-trending secondary faults and associated Mesozoic sedimentation within the depression, while the F1 and F2 faults jointly controlled the development of NE- and near-E-W-trending secondary faults and associated Cenozoic sedimentation. The results indicate that the plate movements and Tanlu episodic, strike-slip faulting generated a left-lateral stress field in the Early Cretaceous, that switched to a right-lateral stress field during the middle Eocene to Oligocene. This transformation produced secondary shear stress fields in the North Yellow Sea Basin and generated NE-trending rifting superimposed on the previous NW-trending rift generation, and controlled the related structural geology and sedimentation in the Eastern depression of the basin. This proposed explanation of a tectonic regime transformation model, coupled with Tanlu strike-slip movements, could also provide new insights into the differences in gaps that occur in the stratigraphic record for the North Yellow Sea Basin and adjacent areas in eastern China. Highlights: The sequence stratigraphy, structure and sedimentation in North Yellow Sea Basin were analyzed. The evolution of the basin was influenced by the Tanlu episodic strike-slip faulting. The tectonic regime transformation pattern in the basin (and eastern China) was proposed. The proposed pattern has further implications for depositional hiatus of basins in eastern China.